Living through liminality? Situating the transitional experience of parents of children with mucopolysaccharidoses. Issue 3 (18th August 2021) - Somanadhan, Suja; Brinkley, Aoife; Larkin, Philip J.
Abstract: Background: Mucopolysaccharidoses (MPS) are rare inherited metabolic disorders that come under category three of life‐limiting conditions. Children born with this condition show no symptoms at birth, but its effects show as a progressive disease in subsequent years. The severity of the condition varies according to the specific type, ranging from very mild symptoms to, in most cases, complex healthcare needs, including mental and physical disabilities. Aims: This study aimed to elucidate the meanings of the transition experience of being a parent of a child with MPS. Van Gennep's three‐stage rite of passage theory and Turner's theory of liminality were utilised to understand these families' transition experiences are learning to live with their child's ongoing progressive illness trajectory. Methods: A qualitative design utilising hermeneutic phenomenology was used. Longitudinal qualitative in‐depth interviews were carried out with eight parents at a three‐time point over 17‐months period. Results: This study provided an interpretation of the lived experience of parents of children and young adults with MPS. As such, it embraces a liminal experience of living with a rare life‐limiting illness and the unique passage to becoming a parent of a child with MPS. Parents reported their experience of transition from being the parent of a normal healthy child to be the parent of a child with MPS. They described their transition experience as multi‐faceted and complex, neither linear nor time‐bound, but rather cyclical. Conclusion: The rites of passage conceptual framework helped to identify specific and significant unmet supportive and social care needs of these families and their children. This information will enhance the development of a substantial support system to meet the family's emotional, psychological and social needs during the illness transitions from diagnosis and throughout their illness journey.